KONSEP PERENCANAAN DALAM MANAJEMEN PENDIDIKAN ISLAM - Amelia Ayu Wanda (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2023)
The necessity to advance high-quality Islamic education underscores the need for appropriate planning concepts within Islamic education management. This journal explores the concept of planning in the context of Islamic education management as an effort to understand the principles that underpin the development of an effective Islamic education system. Within this context, this research delineates various critical aspects, including curriculum development, resource management, quality learning, and evaluation. Through theoretical analysis and case studies, this journal identifies several relevant conceptual approaches that can be employed in Islamic education planning. The significance of integrating Islamic values into the curriculum and teaching methods, as well as efficient resource management, takes center stage in this article. The findings of this research will provide valuable insights for decision-makers in Islamic educational institutions, curriculum developers, and other stakeholders striving to enhance the quality of Islamic education. Sound planning concepts are a crucial foundation for achieving comprehensive and sustainable goals in Islamic education.